Comically Queering Lima: Urban Ecology in Islas (2010) by Rodrigo La Hoz. - Smith, Amanda M. (Revista Hispánica Moderna (0034-9593), 2024)
This essay considers the contemporary comic book's potential to generate an ecological consciousness that reflects on the many forms of heteropatriarchal oppression at the same time that it presents the reading experiences as a way of escaping them. I examine how Limeño artist Rodrigo La Hoz elaborates a queer urban ecology in his 2010 comic book Islas to critique and subvert Lima's normativity. Situating his work in the broader context of Peruvian and Latin American comics reveals it as a critical intervention about the failed attempts to humanize and normativize cities and a call to the creative possibilities of those failures.